Lower Algae in the Kunji Qal’a Sewer of the Bukhara City - Muxtorovich, Qobilov Aziz; Alijonovna, Jo’rayeva Maftuna (American Journal of Biology and Natural Sciences, 2024)
This article provides information about the geographical location of the Kunji Qal’a reservoir flowing through the city of Bukhara, the chemical composition of the water, as well as about micro algae and higher algae found in the reservoir. In the first months of the summer and autumn season, when sunlight will be abundant, there will be favorable conditions for the development and reproduction of algae common in the reservoirs of the Bukhara. The water level in the reservoir rises mainly in the process of land irrigation, as a result of the leaching of salty soils in the fields, in particular in the Bukhara region in 1978, the volume of collector waters amounted to 1,494 million m3.